2016
DOI: 10.1371/journal.pone.0166821
|View full text |Cite
|
Sign up to set email alerts
|

The Association of EGFR Mutations with Stage at Diagnosis in Lung Adenocarcinomas

Abstract: BackgroundThe prognostic role of epidermal growth factor receptor (EGFR) mutations in patients with lung adenocarcinomas remains controversial and the association between EGFR mutations and stage at the time of the initial diagnosis is debatable. In this study, we evaluated the association of EGFR mutations with stage at diagnosis in lung adenocarcinomas.Materials and MethodsWe retrospectively analyzed 1004 consecutive patients who were diagnosed with lung adenocarcinomas and tested for EGFR mutations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Studies have suggested that EGFR mutation rates in patients with lung adenocarcinoma differ among countries and ethnicities, between sexes, and with smoking status ( 25 27 ). The overall mutation rate of EGFR in Chinese patients with lung adenocarcinoma in the present study was 50.7%, which is consistent with previous reports ( 6 , 25 27 ). The mutation rate in female patients was significantly higher than that of male patients (P<0.001) while the mutation rate in smokers was low compared with non-smokers (P=0.003), which was also consistent with previous reports ( 25 , 26 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Studies have suggested that EGFR mutation rates in patients with lung adenocarcinoma differ among countries and ethnicities, between sexes, and with smoking status ( 25 27 ). The overall mutation rate of EGFR in Chinese patients with lung adenocarcinoma in the present study was 50.7%, which is consistent with previous reports ( 6 , 25 27 ). The mutation rate in female patients was significantly higher than that of male patients (P<0.001) while the mutation rate in smokers was low compared with non-smokers (P=0.003), which was also consistent with previous reports ( 25 , 26 , 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Lung adenocarcinoma is the most common subtype of NSCLC, with a high recurrence rate and short survival time ( 4 ). According to previous research, oncogenes serve an important role in the occurrence and development of lung adenocarcinomas, and may be potential therapeutic targets ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in studies of other cancers, GMFs have been found to vary in different stages of cancer. [3637383940] However, to the best of the author's knowledge, this is the first study demonstrating GMF variation in different stages of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 89%
“…Activating EGFR mutations are involved in the pathogenesis of a significant subset of lung adenocarcinomas 11 . The frequency of EGFR mutations in lung adenocarcinomas worldwide varies (from 8–13% in European populations to 27–60% Asian populations) according to ethnicity, gender, and tobacco exposure 12,13 . EGFR gene has emerged as a critical therapeutic target and EGFR mutations status has successfully guided clinical management 14 .…”
Section: Introductionmentioning
confidence: 99%